Diagnostic performance of T1 and T2 mapping to detect intramyocardial hemorrhage in reperfused ST‐segment elevation myocardial infarction (STEMI) patients. Issue 3 (15th February 2017) - Bulluck, Heerajnarain; Rosmini, Stefania; Abdel‐Gadir, Amna; Bhuva, Anish N.; Treibel, Thomas A.; Fontana, Marianna; Gonzalez‐Lopez, Esther; Ramlall, Manish; Hamarneh, Ashraf; Sirker, Alex; Herrey, Anna S.; Manisty, Charlotte; et al.
Abstract : Purpose: To investigate the performance of T 1 and T 2 mapping to detect intramyocardial hemorrhage (IMH) in ST‐segment elevation myocardial infarction (STEMI) patients treated by primary percutaneous coronary intervention (PPCI). Materials and Methods: Fifty STEMI patients were prospectively recruited between August 2013 and July 2014 following informed consent. Forty‐eight patients completed a 1.5T cardiac magnetic resonance imaging (MRI) with native T 1, T 2, and T 2 * maps at 4 ± 2 days. Receiver operating characteristic (ROC) analyses were performed to assess the performance of T 1 and T 2 to detect IMH. Results: The mean age was 59 ± 13 years old and 88% (24/48) were male. In all, 39 patients had interpretable T 2 * maps and 26/39 (67%) of the patients had IMH ( T 2 * <20 msec on T 2 * maps). Both T 1 and T 2 values of the hypointense core within the area‐at‐risk (AAR) performed equally well to detect IMH ( T 1 maps AUC 0.86 [95% confidence interval [CI] 0.72–0.99] versus T 2 maps AUC 0.86 [95% CI 0.74–0.99]; P = 0.94). Using the binary assessment of presence or absence of a hypointense core on the maps, the diagnostic performance of T 1 and T 2 remained equally good ( T 1 AUC 0.87 [95% CI 0.73–1.00] versus T 2 AUC 0.85 [95% CI 0.71–0.99]; P = 0.90) with good sensitivity and specificity ( T 1 : 88% and 85% and T 2 : 85% and 85%, respectively). Conclusion: The presence of a hypointense core on the T 1 and T 2 maps can detect IMH equally well and with good sensitivity and specificity in reperfused STEMI patients and could be used as an alternative when T 2 * images are not acquired or are not interpretable. Level of Evidence : 2 Technical Efficacy: Stage 2 J. MAGN. RESON. IMAGING 2017;46:877–886